O significado social do ensino de língua estrangeira para alunos de escola pública - Santos, Ricardo Luiz dos (2011)
The present work develops the argument that on these times when communication has become world wide; communication, gloabalization of economy, "planetarization" of the international relationships, new challenges are directed to school. Among them, the challenge of placing the goal of insertion/domain by students, in what for excellence concerns the sign of the “global village”, in other words, communication. It is in the ambit of communication, of the exchange between people and cultures, of the globalized information to be apprehended in the world visions and messages transmitted starting from the interests of the political and economical groups to which organically serve, twe placed the importance of learning foreign language(s) . Foreign language that, in the stage lived today by the globalism, has in The English its more expanded vulgata. The aims of foreign language(s) teaching being prioritized as study object, the English language, is located in the ambit of the conception of language as a social phenomenon and the notion of teaching/learning them. Consequently, is located as a practice whose aims don't relapse on the language as a closed system, but as a tool in the construction of a critical conscience of the uses which are done of that language in different social contexts The study also opens a debate about factors that interfere in the learning process of popular individuals, as teaching places, analyzes differentiated conditions in two public schools. Conditions which facilitate the democratization of the access to foreign language, in the ambit of understanding already explained.